2014
DOI: 10.1038/srep06203
|View full text |Cite
|
Sign up to set email alerts
|

Hollandites as a new class of multiferroics

Abstract: Discovery of new complex oxides that exhibit both magnetic and ferroelectric properties is of great interest for the design of functional magnetoelectrics, in which research is driven by the technologically exciting prospect of controlling charges by magnetic fields and spins by applied voltages, for sensors, 4-state logic, and spintronics. Motivated by the notion of a tool-kit for complex oxide design, we developed a chemical synthesis strategy for single-phase multifunctional lattices. Here, we introduce a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 58 publications
0
38
0
Order By: Relevance
“…S9). Moreover, the selfcollection strategy has been successfully applied to synthesize other complex metal oxides 15 .…”
Section: Discussionmentioning
confidence: 99%
“…S9). Moreover, the selfcollection strategy has been successfully applied to synthesize other complex metal oxides 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Structural characterization including electron microscopy revealed that it contains Mn 4þ and Mn 3þ and exhibits correlated antiferromagnetic and ferroelectric order. 20 One-dimensional ZnMn 2 O 4 nanowires exhibited high power capability at elevated current rates, attributed to enhanced kinetics of the nanowire electrode. 21 Fundamental studies involving the impact of physical and chemical properties of materials on their electrochemical properties are critical to the rational development of battery materials which may address the present and future requirements for stationary and portable power.…”
mentioning
confidence: 99%
“…The value of maximum polarization, P max = 13.83 and 8.28 μC/cm 2 , and remanent polarization, P r = 5.45 and 2.46 μC/cm 2 with coercivity, E c = 9.53 and 6.14 kV/cm, respectively, measured for BFTO:Ce and BFTO:La. These values of polarization have an improvement than reported work on single‐phase multiferroic . This is due to nanoaggregation formation and lattice distortion enhancement in the BTO lattice.…”
Section: Resultsmentioning
confidence: 49%